Diversion policy against children in conflict with internal law serious crime based on justice value - Ismail Pettanasse,; Teguh Prasetyo,; Otto Yudianto, (Technium Social Sciences Journal, 2021)
This type of research in legal research is normative or doctrinal legal research. The diversion policy against children who are in conflict with the law in criminal cases punishable by 7 (seven) years based on the value of justice is limited by the existence of Article 7 paragraph 2 which states that diversion is carried out in the event that the offense committed is punishable by imprisonment under 7 (seven) years, so that the existence of Article 7 paragraph (2) has limited the implementation of diversion itself, and this is clearly contrary to the principles of the implementation of the child protection law, because this limitation isn’t the best principle for children.